Impact of teachers’ professional development on school improvement—an analysis at Bangladesh standpoint - Hoque, Kazi Enamul; Alam, Gazi Mahabubul; Abdullah, Abdul Ghani Kanesean (Springer Verlag, 2011)
This study seeks to describe the teachers’ professional development activities in Bangladesh and explores the hypotheses about the relationship between teachers’ traditional professional development activities and school improvement. Data from a representative sample of City secondary schools from Bangladesh (n = 127) were gathered through questionnaires from 127 principals and 694 teachers. Hierarchical multiple regression analysis was used in this research. This study found significant impacts of some of teachers’ professional development activities on school improvement. Also found that the maximum school improvement can be achieved if schools put more emphasis on teachers’ collaboration, in-service training and classroom observation and less emphasis on individual action enquiry. The findings of this study provide important information for the policy makers, educational managers and especially for the headmasters and teachers concerned with the improvement of teachers’ quality in secondary schools of Bangladesh. This study adopts a concurrent approach of data collection and analysis.